2021
DOI: 10.1021/acsomega.1c02559
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonds and n → π* Interactions in the Acetylation of Propranolol Catalyzed by Candida antarctica Lipase B: A QTAIM Study

Abstract: Enzyme−substrate interactions play a crucial role in enzymatic catalysis. Quantum theory of atoms in molecules (QTAIM) calculations are extremely useful in computational studies of these interactions because they provide very detailed information about the strengths and types of molecular interactions. QTAIM also provides information about the intramolecular changes that occur in the catalytic reaction. Here, we analyze the enzyme−substrate interactions and the topological properties of the electron density in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…Furthermore, through 13 C NMR titrations and DFT calculations, it was revealed that the catalyst can form complexes with substrates, thereby catalyzing the respective reactions (Figure 15c). Doerr and coworkers [26] set up a quantum theory of atoms in molecules (QTAIM) and natural bond orbital analysis to analyze the enzyme-substrate interactions in acylation of (R,S)propranolol catalyzed by Candida antarctica lipase B. The optimized tetrahedral intermediate structure of enzyme and propranolol enantiomers indicated n!π* interactions between the OH oxygen of propranolol and the carbonyl group of the acyl serine in the Michaelis complex (MCC), and between the OH oxygen of serine and the carbonyl group of the acylated propranolol in the enzyme product complex (EPC).…”
Section: Catalysismentioning
confidence: 99%
“…Furthermore, through 13 C NMR titrations and DFT calculations, it was revealed that the catalyst can form complexes with substrates, thereby catalyzing the respective reactions (Figure 15c). Doerr and coworkers [26] set up a quantum theory of atoms in molecules (QTAIM) and natural bond orbital analysis to analyze the enzyme-substrate interactions in acylation of (R,S)propranolol catalyzed by Candida antarctica lipase B. The optimized tetrahedral intermediate structure of enzyme and propranolol enantiomers indicated n!π* interactions between the OH oxygen of propranolol and the carbonyl group of the acyl serine in the Michaelis complex (MCC), and between the OH oxygen of serine and the carbonyl group of the acylated propranolol in the enzyme product complex (EPC).…”
Section: Catalysismentioning
confidence: 99%